1991
DOI: 10.1128/jb.173.16.5068-5078.1991
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of repression and activation of the tyrP gene in Escherichia coli

Abstract: In a previous report it had been suggested that the tyrP gene of Escherichia coli may be expressed from two separate promoters. We have endeavored to confirm this suggestion by primer extension studies and the separate subcloning of each of these promoters. In these studies, we found a single promoter whose expression was repressed by TyrR protein in the presence of tyrosine and activated by TyrR protein in the presence of phenylalanine. Two adjacent TYR R boxes, with the downstream one overlapping the tyrP pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
65
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 27 publications
3
65
0
Order By: Relevance
“…This will be discussed separately later. Mutational studies have confirmed the critical role of the 'weak' box in the repression of three of the four transcription units, namely uroF-tyrA, tyrP and tyvB (Cobbett & Delbridge 1987;Yang & Pittard 1987;Andrews et al 1991b). Similar studies have shown that the 'weak' box of avoL is not required for repression (Lawley & Pittard 1994).…”
Section: Binding Of the Aromatic Amino Acids To Tyrr Proteinsupporting
confidence: 50%
“…This will be discussed separately later. Mutational studies have confirmed the critical role of the 'weak' box in the repression of three of the four transcription units, namely uroF-tyrA, tyrP and tyvB (Cobbett & Delbridge 1987;Yang & Pittard 1987;Andrews et al 1991b). Similar studies have shown that the 'weak' box of avoL is not required for repression (Lawley & Pittard 1994).…”
Section: Binding Of the Aromatic Amino Acids To Tyrr Proteinsupporting
confidence: 50%
“…It also requires an adjacent strong box. The inactivation of this box abolishes protection of both boxes, except at high concentrations of TyrR protein, and results in the loss of TyrR-mediated regulation of both genes (1,2,16,25). In tyrP, the tyrosine-mediated cooperative binding results in repression, whereas in mtr, because of the different placement of the second TYR R box, it results in a further increase in activation.…”
mentioning
confidence: 99%
“…In the case of tyrP, this weak box is separated by 1 bp from the strong box and lies downstream, overlapping the RNA polymerase binding site (1,2). In the case of mtr, it is situated 8 bp upstream of the strong box and well clear of the RNA polymerase binding site.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmids pHYD272, pHYD275, pHYD283, and pHYD284 have been described earlier (6) and are a panel ofproU-bearing derivatives of the low-copy-number promotercloning vector pMU575 that contains 1acZ+ as the reporter gene and encodes Tpr as the antibiotic resistance marker (2).…”
mentioning
confidence: 99%